Answer:
The height jumped by the person on the moon is 6 times the height jumped by the person on earth.
Explanation:
As we know that the acceleration due to gravity on moon is 1/6 of the acceleration due to gravity on earth.
So, it is false.
Let the mass of man is m and the gravity on moon is g' = g/6.
Let the height jumped on earth is h and the height jumped on moon is h'.
So,
m x g' x h' = m x g x h
g/6 x h' = g x h
h' = 6 h
So, the height jumped by the person is 6 times the height jumped by the person on earth.